Angiosarcoma of the Right Atrium Presenting as Syncope and Hemorrhagic Pericardial Tamponade. (5th November 2012) - Sams, V. G.; Tsapenko, A.; Kravitz, J. N.; Gaines, T. E.
Abstract : Angiosarcoma of the heart is a rare malignancy that can present in many ways. It is an important diagnosis to consider in patients presenting with otherwise unexplained tamponade-type symptoms. Here we present a case of a young male who presented with hemorrhagic tamponade and underwent resection of a large angiosarcoma of the right atrium. In this case, we describe the rare presentation of angiosarcoma with its diagnostic approaches, hospital course, clinical management, and discussion.